What is memory? The present state of the engram. Issue 1 (December 2016) - Poo, Mu-ming; Pignatelli, Michele; Ryan, Tomás; Tonegawa, Susumu; Bonhoeffer, Tobias; Martin, Kelsey; Rudenko, Andrii; Tsai, Li-Huei; Tsien, Richard; Fishell, Gord; Mullins, Caitlin; Gonçalves, J.; et al.
Abstract The mechanism of memory remains one of the great unsolved problems of biology. Grappling with the question more than a hundred years ago, the German zoologist Richard Semon formulated the concept of the engram, lasting connections in the brain that result from simultaneous "excitations", whose precise physical nature and consequences were out of reach of the biology of his day. Neuroscientists now have the knowledge and tools to tackle this question, however, and this Forum brings together leading contemporary views on the mechanisms of memory and what the engram means today.